Distinct Nutrient Intake Style in Inhabitants of Ultra-High-Altitude Areas in North of Tibet, China: A Cross-Sectional Study Based on Newly Developed Tibetan Food Frequency Questionnaires - Xiao, Zhen; Sun, Xianzhi; Zhaxi, Duoji; Zhang, Fan; Ji, Yuchen; Cheng, Tingting; Li, Xiaofeng; Xu, Xiaoguang (Frontiers in Nutrition, 2021)
Dietary pattern is quite distinct among the inhabitants of high-altitude areas because of environmental and geographical uniqueness; hence, it is important to investigate this data as accurately as possible. However, very few data are related to these populations up to now. Based on the food frequency questionnaire (FFQ) used in the Chinese population, a revised Tibetan edition was developed with respect to the life style in high-altitude areas. After assessment of validity and reproducibility, a nutrition intake survey was conducted among 1,071 randomly sampled Tibetan people. In addition, the Bland–Altman approach was used to compare the agreement between the two dietary tools. For the reproducibility analysis, intra-class correlation coefficients (ICC) were calculated to examine the agreement of food groups and nutrients from the two FFQs (FFQ1 and FFQ2). Nutrient intake was calculated using food composition tables. For the validity analysis, Pearson’s correlation of food groups intakes varied from 0.22 to 0.91 (unadjusted). The correlations of nutrients ranged from 0.24 to 0.76 (unadjusted). In the analysis of reliability, the ICC of food groups varied from 0.27 to 0.70 (unadjusted). The ICC of nutrient intakes ranged from 0.22 to 0.87 (unadjusted). The results of nutritional analysis showed that approximately 25% of foods consumed frequently were traditional Tibetan foods. However, traditional Han foods were frequently consumed as well. In addition, the energy, iron, and protein intakes for male or female subjects was close to the Chinese Dietary Nutrient Reference Intake (Chinese DRIs); however, fat and sodium intakes were significantly higher than the Chinese DRIs. Interestingly, lower intakes of other types of nutrition such as vitamin C were detected in people living in high-altitude areas. Our data indicated that excess consumption of fat and sodium and insufficient intake of vitamin C were common among Tibetan people, as compared with most Chinese people living in the plateau areas. More investigations are needed to reveal the association between the food intake style and high-altitude endemic diseases.